Examining the Impact of Intercultural Education on the Levels of Intercultural Sensitivity of Primary School Teachers: Evidences From North Macedonia - Adili, Bujar; Zenki-Dalipi, Arbresha; Ameti, Makfirete (Pedagogika, 2024)
The research aims to examine whether the intercultural education teachers’ previous experience affects their level of intercultural sensitivity. The research results show that prior intercultural education significantly affects the levels of ethnocentrism and ethnorelativism of teachers. Considering the results, which show that intercultural education does not impact teachers’ substantive knowledge and perceptual understanding, educational authorities should seek alternative ways to enhance it.